1905. Real-World Insights into Quality Improvement across 11 HIV Clinics in the United States. (26th November 2018) - Wohl, David Alain; Brinson, Cynthia; Hicks, Charles; Shalit, Peter; Hardy, W David; Carter, Jeffrey; Simone, Laura; Sapir, Tamar
Abstract: Background: As people with HIV are living longer, focusing quality improvement (QI) initiatives on health maintenance and comprehensive patient-centered care is essential. This QI study evaluated chart-document performance in selected HIV care practices across the United States. Methods: Participants were randomly selected from 11 Ryan White-funded HIV clinics in community ( n = 7), hospital ( n = 3), and academic ( n = 1) settings. At baseline, 200 consecutive charts ( 20 per clinic) were reviewed for documentation of guideline-directed practices. Clinic teams participated in audit-feedback interventions to develop improvement plans. Three months later, consecutive charts were reviewed according to baseline methods. Chi-square tests were conducted to analyze pre- and post-intervention differences. Results: Significant improvements were seen in sexually transmitted infection (STI) screening, and patient counseling on sexual risk, pre-exposure prophylaxis (PrEP), and antiretroviral therapy (ART). Documentation of several health maintenance measures improved significantly. Conclusion: Audit-feedback of QI measures improved performance. This approach can inform future QI initiatives. Disclosures: C. Brinson, Gilead: Investigator, Scientific Advisor and Speaker's Bureau, Research support and Speaker honorarium. Theratech: Investigator, Research support. BMS: Investigator, Research support. SlieaGen: Investigator, Research support. GSK ViiV: Consultant, Investigator and Scientific Advisor, Consulting fee, Research support and Speaker honorarium. Daiichi Sankyo: Sub Investigator, Research support. Novo Nordisk: Investigator, Research support. Sanofi: Investigator, Research support. Watson: Investigator, Research support. Salix: Investigator, Research support. Janssen: Investigator, Research support. Roche: Investigator, Research support. Colucid: Investigator, Research support. Eisai: Investigator, Research support. Shionogi: Investigator, Research support. Elcelyx: Investigator, Research support. Sangamo: Sub Investigator, Research support. C. Hicks, ViiV Healthcare: Employee, Salary. P. Shalit, Gilead: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium. Viiv: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium. Janssen: Consultant, Investigator and Speaker's Bureau, Research support and Speaker honorarium. Merck: Speaker's Bureau, Speaker honorarium. W. D. Hardy, Gilead Sciences: Consultant and Investigator, Consulting fee and Research support. ViiV Healthcare: Consultant and Investigator, Consulting fee and Research support. Amgen: Investigator, Research support. Janssen: Investigator, Research support. Merck: Investigator, Research support. J. Carter, PRIME Education, LLC: Employee, Salary. L. Simone, PRIME Education, LLC: Employee, Salary. T. Sapir, PRIME Education, LLC: Employee, Salary. Gilead Sciences Inc.: Independent medical education provider, Educational grant.